GAMIFICATION AS AN EFFECTIVE TOOL IN TEACHING ENGLISH. (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the use of gamification as an innovative and effective approach to teaching English. Gamification, the integration of game elements into non-game contexts, has proven to increase learner engagement, motivation, and performance in language classrooms. The paper discusses the theoretical background of gamification, its key components, pedagogical benefits, practical applications, and challenges in English Language Teaching (ELT). It concludes that gamification not only motivates students but also enhances communication, creativity, and critical thinking in language learning environments.